Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation dalam Menumbuhkan Kemandiriran Belajar Siswa SMAN 7 Banjarmasin - Zaitunnah, Zaitunnah; Hasanah, Mahmudah; Rizky, Maulana; Ratumbuysang, Monry Fraick Nicky Gillian (Universitas Negeri Surabaya, 2024)
Independence in students will influence student achievement at school, one effort is to increase student learning independence through learning changes by implementing the group investigation (GI) type cooperative learning model. This research aims to determine the effect of the group investigation type cooperative learning model in increasing student learning independence at SMA Negeri 7 Banjarmasin. This research uses quantitative methods with descriptive research type. Sampling used a purposive sampling technique, namely 260 students. The data analysis technique uses SMART PLS Version 3.2.9. The results of the research found that there was a positive and significant influence between the application of the investigative group type cooperative learning model on the learning independence of students at SMA Negeri 7 Banjarmasin.